Performance Analysis of CO2 Systems Integrated with Ejector and Dedicated Mechanical Subcooling - Dai Baomin; Zhao Ruirui; Liu Shengchun; Qian Jiabao; Xu Tianyahui; Liu Chen; Yang Peifang (Zhileng xuebao)
A transcritical CO2 system combined with an ejector and dedicated mechanical subcooling (EJ-DMS) was developed to improve the performance of the CO2 system in the space heating and cooling of buildings throughout the year. A thermodynamic model of the system was devised. Then, the discharge pressure and subcooling degree were optimized using a genetic algorithm by considering the coefficient of performance (COP) as the objective function. Using five typical cities as application scenarios, the energy consumption and annual performance factor (COPann) of the system were analyzed. The results show that, compared with a conventional mechanical subcooling system and the conventional ejector system, the heating COP of EJ-DMS is enhanced by 10.90% and 5.58%, respectively, and the cooling COP is increased by 8.99% and 18.12%, respectively. The COPann values are improved by 7.95% and 5.98%, respectively. Compared with the conventional ejector system, the discharge pressure of EJ-DMS is reduced by 0.47 MPa and 0.77 MPa in the heating and cooling modes, respectively. In addition, the COPann improvement ratio of the EJ-DMS system is the highest when operating in Guangzhou and Harbin, indicating that the EJ-DMS system is more suitable for regions with relatively high or low ambient temperatures, such as hot summer and warm winter or severely cold regions. This study provides a theoretical reference for the development and optimization of a combined cooling and heating CO2 system.